An Analytical Study Between 9Th to 12Th Century of Chadels Famous Bettles In Bundelkhand: The Impact of the Rise of Buddhism on Religious Practices in 9th to 12th Century Chadels Famous Battles in Bundelkhand (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The rise of Buddhism affected a significant revolution inBuddhism, both in thought and practice. The term Buddhism is, literally, thegreat vehicle or the highest means or the complete doctrine. The new movementis called thus for universal salvation as the kernel of it. It is large enoughto carry all beings to the absolute or real happiness. It invites all to aspirefor the highest goal of the Buddha-hood without exception of laity. It’sout-look is broad and its aim is infinitely great like the infinite sky. Itscapacity can accommodate various religious beliefs and popular practice.Moreover Sanskrit language,which is considered as the divine language of scripture, was used for itswritings.